Hubungan antara Risiko 4 Terlalu dan Kepatuhan Antenatal Care (ANC) dengan Komplikasi Persalinan - Kartikasari, Rina; Rohani, Siti; Irianti, Susi (Universitas Faletehan, 2025)
Complications during childbirth are one of the leading causes of maternal mortality in Indonesia. This condition arises from high-risk pregnancies or deliveries and can threaten the lives of both the mother and the fetus, necessitating appropriate obstetric management. This study aims to determine the relationship between the 4 too much (4T) risks and antenatal care (ANC) compliance with labor complications at Baros Health Center in Serang Regency, Banten Province, Indonesia. This research employed an analytical design with a case-control framework. A total of 292 respondents were randomly selected as samples. Data were collected from annual report books, delivery registers, and e-cohorts. Data analysis was conducted using the chi-square test. The results indicated that the incidence of childbirth complications occurred in 55.5% of the total respondents, with hemorrhage being the most common type of complication (34% of 162 complication cases). The occurrence of complications had a significant relationship with being too young (p=0.000; OR=9.8), being too old (p=0.000; OR=16.9), having too many children (p=0.000; OR=20.3), too close birth distance (p=0.000; OR=7.5), and ANC compliance (p=0.000; OR=62.2). The most significant risk factor was ANC compliance. Based on the study's findings, promotional and preventive efforts need to be enhanced through education on the importance of ANC compliance for pregnant women. Additionally, family planning programs should be strengthened to prevent pregnancies at too young or too old ages, manage the number of children, and ensure ideal birth spacing.